(untitled) (Buana Pendidikan: Jurnal Fakultas Keguruan dan Ilmu Pendidikan Unipa Surabaya, 2025)
This study aims to analyze the application of the song media "Ayo Sinau Basa Ngoko lan Krama" to improve the understanding of first grade elementary school students about Javanese language etiquette at SD N 4 Banjaran. The main problem is the low use of Javanese ngoko and krama in daily communication, due to the habit of using Indonesian and ngoko without etiquette. Through interactive singing learning, students find it easier to understand the difference between ngoko and krama. The song media was chosen because it is fun and easy to remember. The results of the study showed an increase in students’ understanding of Javanese language etiquette, with scores that were previously below the KKM now increasing above the KKM, indicating the effectiveness of songs as a fun and interactive learning media.